Chemical Study of Asphaltene Inhibitors Effects on Asphaltene Precipitation of an Iranian Oil Field - Masoud Riazi; Hossein Rezaei; Mohsen Mansouri; Behrouz Bayati; Afshar Ahmadbaygi; Afshar Ahmadbaygi (IFP Énergies nouvelles, 2020)
The study evaluates the effectiveness of commercial asphaltene inhibitors on crude oil from an Iranian field. Using two n-paraffin solvents (n-heptane, n-hexane) and FTIR spectroscopy, they determine Asphaltene Onset Point (AOP). Without inhibitors, AOP occurs at 35 vol.% n-heptane; with 3000 ppm of inhibitor B, AOP shifts to 60 vol.%. Efficiency depends on oil pH and inhibitor chemical structure.
Keywords: type of access: open access; FTIR spectroscopy; oil field; asphaltene precipitation; inhibitors; asphaltene; asphaltene